Recent Labour Market Trends in the Visegrad Group Countries; Tendencje zmian na rynku pracy w krajach Grupy Wyszehradzkiej - Eugeniusz Kwiatkowski (Comparative Economic Research. Central and Eastern Europe, 2011)
This study analyses labour market trends that appeared in Poland and other Visegrad Group countries during the global economic crisis, i.e. between 2007 and 2009. Special attention is paid to the changes in employment and unemployment rates that occurred in that period. For the sake of comparison, the labour market indicators are contrasted with average rates for the European Union and the euro area. The presented analysis aims to identify the degree to which unemployment rates and indicators of employment changed in the selected countries in response to the global crisis and to explain why the labour markets in the sample countries reacted differently. It also addresses the changing production volumes and labour market flexibility, particularly towards wages, employment and working time. The above analyses show that the labour markets of the Visegrad Group countries changed significantly during the global economic crisis, i.e. between 2007 and 2009; unemployment rates rose, while volumes and rates of employment decreased. In Poland, the two indicators changed their values relatively insignificantly, but in Hungary, Slovakia and the Czech Republic the changes were quite distinct. In the crisis years, Polish employment fell and unemployment increased to a relatively small degree. Although the main reason for this was the quite favourable growth trend in the Polish GDP, cuts in real wage and working time reductions also played a role. The relatively marked decline in the Hungarian employment is maliny attributed to the strong downward trend in the country's GDP, but the decline would have probably been much more extensive, if not for the reductions in working time, real wages and labour productivity. The large declines in the Slovak and Czech employment appeared because the countries' GDPs grew smaller while real wages grew bigger. Shorter working hours and limitations on labour productivity that the two countries introduced could not reverse the unfavourable employment trends that occurred during economic downturn. – – Artykuł podejmuje analizy tendencji na rynku pracy w Polsce i innych krajach Grupy Wyszehradzkiej w okresie globalnego kryzysu lat 2007-2009. Szczegoĺna uwaga posẃiecona jest zmianom wskazńikoẃ zatrudnienia i bezrobocia. Dla celoẃ poroẃnawczych wskazńiki skonfrontowano z przecietnymi wskazńikami dla Unii Europejskiej i strefy euro. Analiza ma na celu okresĺenie skali zmian stoṕ bezrobocia i zatrudnienia w relacji na globalny kryzys oraz objasńienie dlaczego reakcje te były zroźṅicowane w badanych krajach. W objasńieniu zwraca sie uwage na zmiany produkcji oraz elastycznosći rynku pracy, zwłaszcza w odniesieniu do płac, wydajnosći pracy i czasu pracy. Analizy dowodza, zė sytuacja na rynkach pracy w krajach Grupy Wyszehradzkiej zmieniła sie zasadniczo w okresie globalnego kryzysu lat 2007-2009: stopy bezrobocia wzrosły, zasśtopy zatrudnienia spadały. W Polsce oba wskazńiki zmieniły sie nieznacznie, zasńa Wegrzech, w Słowacji i Czechach zmieniły sie istotnie. Zmiany zatrudnienia i bezrobocia w Polsce były nieznaczne głoẃnie z powodu korzystnych tendencji wzrostowych PKB, ale takzė z powodu redukcji płac realnych i czasu pracy. Znaczace spadki zatrudnienia na Wegrzech były spowodowane obnizk̇ami PKB; spadek zatrudnienia byłby wiekszy, gdyby nie redukcje czasu pracy, płac realnych i wydajnosći pracy. Duzė spadki zatrudnienia w Słowacji i Czechach były zwiazane ze słabym wzrostem PKB i silnym wzrostem płac realnych. Redukcje czasu pracy i wydajnosći pracy nie były w stanie odwroćicńiekorzystnych tendencji w zatrudnieniu.
Keywords: 330